2020
DOI: 10.1097/qai.0000000000002345
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Proportion and Disparities of HIV PrEP Use Among Key Populations Identified in the United States National Goals: Systematic Review and Meta-analysis of Published Surveys

Abstract: Background: Pre-exposure prophylaxis (PrEP) use among populations most vulnerable to HIV as identified in the national HIV prevention goals is not fully known. This systematic review assessed trends of lifetime self-reported PrEP use and disparities among key populations. Methods: We used the CDC HIV/AIDS Prevention Research Synthesis cumulative database of electronic and manual searches in MEDLINE, CINAHL, EMBASE, and PsycINFO from 2000 to 2019 to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 17 publications
2
24
1
Order By: Relevance
“…PrEP awareness and referral were higher among Hispanic MSM and transgender persons than among those in other population groups. This finding is consistent with other studies that have documented higher PrEP coverage among MSM and transgender persons ( 3 , 5 ). Given that HIV incidence and prevalence are substantially higher among MSM and transgender persons ( 1 , 6 ), efforts to further increase PrEP awareness and referral among these populations are important to reach persons who might benefit from a PrEP prescription.…”
Section: Discussionsupporting
confidence: 93%
“…PrEP awareness and referral were higher among Hispanic MSM and transgender persons than among those in other population groups. This finding is consistent with other studies that have documented higher PrEP coverage among MSM and transgender persons ( 3 , 5 ). Given that HIV incidence and prevalence are substantially higher among MSM and transgender persons ( 1 , 6 ), efforts to further increase PrEP awareness and referral among these populations are important to reach persons who might benefit from a PrEP prescription.…”
Section: Discussionsupporting
confidence: 93%
“…Although we were unable to directly compare rates of PrEP counselling to other groups, the very low rates of PrEP counselling and prescription among this cohort are consistent with other studies that have shown inequitable PrEP care continuum outcomes among Black individuals [ 7 , 16 , 61 , 63 , 64 ] and highlight the urgent need to ensure equitable PrEP access among this priority population or risk potentiating existing HIV disparities rather than alleviating them. Further investigation is warranted to identify and remove barriers to provider‐, clinic‐ and system‐level PrEP implementation.…”
Section: Discussionsupporting
confidence: 72%
“…Per CDC guidelines, a bacterial STI diagnosis in the previous 6 months was an indication due to sexual risk behaviour [ 6 , 9 ]. Although youth account for a disproportionate number of incident HIV and bacterial STI infections, PrEP use among U.S. youth remains limited [ 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a strong safety profile and high efficacy for preventing HIV, uptake of PrEP has been slow and uneven in the US [ 14 , 15 ]. In addition, among those who do initiate PrEP, significant racial and ethnic disparities exist, with African American and Hispanic individuals being much less likely to use PrEP than White individuals, despite their higher HIV risk [ 16 ].…”
Section: Introductionmentioning
confidence: 99%